AGE OF PHOSPHORITES FROM THE KHUBSUGUL BASIN (MONGOLIA) - Demidenko Y.E.; Zhegallo E.A.; Parkhaev P.Y.; Shuvalova Y.V. (My University, 2003)
The age of phosphorites from the Khubsugul Basin, which is now estimated to be the Late Vendian–Cam-brian, has been debated in geological publications for a long time. New paleontological data provide, at last, reliable evidence favoring the Tommotian age of the Khesen productive formation. Phosphorite-bearing sequences were discovered in the Lake Khubsugul area by Soviet geologists in the mid-1960s [1]. It appeared that the Khubsugul Basin represents one of the largest phosphorite basins of the world. The almost half-century-long study resulted in the establishment of its geological structure and detailed mapping, as well as stratigraphic subdivision and paleontological substantiation of sequences in the basin [2–8]. In the present-day tectonic structure of northern Mongolia, the Khubsugul Basin represents a synclino-rium composed of Upper Riphean–Cambrian sequences. These sequences are represented by the thick Darkhat (probably Upper Riphean) and Khubsu-gul (Vendian–Lower Cambrian) terrigenous–carbonate groups. The latter group is overlain by the Lower Cam-brian Ukhutologoi tuffaceous–terrigenous formation (Fig. 1). The Khubsugul Group consists of three (Ongolik, Khesen, and Erkhelnur) formations. The Khesen phosphorite-bearing formation includes lower carbonate (limestones and calcareous shales), middle productive (with several phosphorite levels), and upper carbonate (limestones and dolomites) members. The sediments are relatively impoverished in organic remains. Therefore, the age of the Khesen For-mation is mainly based on its position in the section taking into account the following facts: the underlying Ongolik Formation encloses the Yudomian microphy-toliths [8], whereas the overlying Erkhelnur Formation has several levels with the Atdabanian trilobites and archaeocyatheans [2, 6, 8]. Microphytolith assem-blages have been recorded [9] in all three members of the Khesen Formation (Fig. 1), whereas spherical zooproblematics and bacteria are registered only in its middle member [8]. Most of the forms discovered are known from the uppermost Precambrian–lowermost Cambrian sequences, but Tasmanites and Osagia senta are missing from the pre-Tommotian rocks [8]. Although no organic remains were previously known in the lower member of the Khesen Formation, its age was usually considered as Tommotian [8, 10, 11].